Looking down Broadway, Skagway, ca. 1914 - Curtis, Asahel, 1874-1941 (1914)
Shows advertising for Draper & Co.Photographers on the right. Handwritten on verso: Skagway. PH Coll 519.29068 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number